Partisipasi Masyarakat Dalam Pengembangan Desa Wisata Sumber Suko (Studi Kasus di Desa Ngreco, Kecamatan Kandat, Kabupaten Kediri) - Anggi Dinda Melly Noviani (CV Putra Publisher, 2023)
The aim of this research is to determine the best tourism development strategy for Ngreco Village. This research uses a qualitative approach with a descriptive approach. The results showed that the best method for developing Sumber Suko Tourism Village in Ngreco Village was to study the potential of natural and man-made tourism in Ngreco Village to increase tourist attraction. Ngreco Village has a unique physical rural natural environment, a rich natural beauty of tourism, and the social life of its inhabitants, all of which are naturally and attractively packaged so that the attractiveness of the countryside can encourage tourist visits. Sumber Suko, which is located in Ngreco Village, Kandat District, Kediri Regency, East Java, is one of the locations with natural resource potential that needs to be further developed due to its strategic location and potential springs. The potential of this natural resource has begun to be exploited by the surrounding community as one of the tourism symbols of Ngreco Village. With the main goal of improving the village economy, there are problems that hinder the development of tourism in the Sumber Suko Tourism Village, such as the not yet optimal provision of facilities and infrastructure at tourist sites, the lack of coordination between the Manager of the Sumber Suko Tourism Village and the management. Local government, and community-based community empowerment have not been optimal. tourism managers, and the lack of opportunities for local communities in Ngreco Village to market MSME products